2005
DOI: 10.1007/s10546-004-9241-4
|View full text |Cite
|
Sign up to set email alerts
|

The urban boundary-layer field campaign in marseille (ubl/clu-escompte): set-up and first results

Abstract: The UBL/CLU (urban boundary layer/couche limite urbaine) observation and modelling campaign is a side-project of the regional photochemistry campaign ESCOMPTE. UBL/CLU focuses on the dynamics and thermodynamics of the urban boundary layer of Marseille, on the Mediterranean coast of France. The objective of UBL/CLU is to document the four-dimensional structure of the urban boundary layer and its relation to the heat and moisture exchanges between the urban canopy and the atmosphere during periods of low wind co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(120 citation statements)
references
References 43 publications
4
104
0
8
Order By: Relevance
“…This study has shown that the ARPS-LAICa model setup is able to satisfactory simulate the flux differences between urban and rural areas, especially by using the thermal roughness length parameterization of Zilitinkevich et al [1992] and a thermal admittance value m of 1206.23 J m À2 s 1/2 K À1 . Moreover, comparisons with more complex models as the TEB/ISBA scheme over the same terrain [Mestayer et al, 2005] shows that using this simple approach, same magnitude of flux errors compared to observations are obtained. Moreover, comparison to a study done by Lemonsu et al [2004] shows that our simple model setup generates results for the surface fluxes (in terms of RMSE) similar to that of TEB-ISBA using a single urban class as defined in the CORINE land cover classification (as used in this study) over Marseille.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…This study has shown that the ARPS-LAICa model setup is able to satisfactory simulate the flux differences between urban and rural areas, especially by using the thermal roughness length parameterization of Zilitinkevich et al [1992] and a thermal admittance value m of 1206.23 J m À2 s 1/2 K À1 . Moreover, comparisons with more complex models as the TEB/ISBA scheme over the same terrain [Mestayer et al, 2005] shows that using this simple approach, same magnitude of flux errors compared to observations are obtained. Moreover, comparison to a study done by Lemonsu et al [2004] shows that our simple model setup generates results for the surface fluxes (in terms of RMSE) similar to that of TEB-ISBA using a single urban class as defined in the CORINE land cover classification (as used in this study) over Marseille.…”
Section: Discussionmentioning
confidence: 73%
“…The difference in MAE and RMSE are of the same order of magnitude, which proof that those errors in heat storage flux by using the RES method are not responsible for the variances in the sensible heat flux. Comparing these result with the more complex TEB-ISBA model setup, thereby using observed forcing to run in offline mode, results for the heat storage flux are of the same order of error magnitude with a RMSE of 66.2 and 71.1 for the complex TEB/ISBA scheme and our reference run respectively Mestayer et al, 2005].…”
Section: Heat Fluxesmentioning
confidence: 64%
See 2 more Smart Citations
“…1). A second reason is the availability of a large measurement dataset collected in the frame of the ESCOMPTE projet in 2001 (Cros et al 2004;Mestayer et al 2005) and available for model evaluation.…”
Section: Introductionmentioning
confidence: 99%